Institutional shareholder activism in Nigeria: An accountability perspective. Issue 2 (June 2016) - Uche, Chinyere O.; Adegbite, Emmanuel; Jones, Mike
Highlights: This study employs a qualitative methodology. This study critically evaluates the perceptions of active and passive institutional shareholders. It captures their perception on the value of shareholders' associations' participation in shareholder activism. It draws on three features of accountability in shareholder activism. The feature includes; dialectical activity, independence and agenda. Abstract: Research has identified institutional shareholders and shareholders' associations as separate groups that are able to interact and promote accountability through shareholder activism. This study employs a qualitative methodology to critically evaluate how institutional shareholders perceive the participation of Nigerian shareholders' associations in shareholder activism. We examine three features of accountability that are vital in shareholder activism; dialectical activity, independence and agenda. We contribute to the accountability literature by showing how these three features shape institutional shareholders' perception of shareholders' associations as shareholder activists. Our findings show distinct differences between the views of representatives from active and passive institutional shareholders.